Inverse Limit of an Inverse System of BE-algebras (European Journal of Pure and Applied Mathematics, 2021)
This paper covers the notion of the inverse limit of an inverse system of BE-algebras and investigates some of its properties. Moreover, this study deals with the completion of a BE-algebra.